Molecular Identification of Indigenous Lactic Acid Bacteria, Partial Purification and Characterization of β-Galactosidase Produced - Khusniati, Tatik; ., Sulistiania; Pamela Fury, Bellen Nastitie; Falah, Syamsul; Choliq, Abdul (KnE Life Sciences, 2017)
β-Galactosidase is enzyme which hydrolyze lactose to glucose and galactose, as lactose hydrolyzer. To know indigenous lactic acid bacteria (LAB) characteristics, indigenous LAB identification, partial purification and characterization of β-galactosidase produced was researched. LAB was molecularly identified, β-galactosidase partial purification was conducted by precipitation followed dialysis. β-Galactosidase characterization was based on optimum activities of pH and temperature. The results show that LAB was identified as Lactobacillus plantarum B123. Optimum activity of precipited β-galactosidase was reached at 50 % ammonium sulphate. Activity and specific activity of 50 % precipited β-galactosidase were 95.675 U · mg–1 and 32.268 U · mg–1, respectively. Precipited β-galactosidase resulted a purification level of 3.99 fold, a yield of 38.73 %, and a specific activity of 32.27 U · mg–1 protein, while dialyzed β-galactosidase resulted 7.61 fold, 10.67 %, and 61.53 U· mg–1 protein. Optimum temperature and pH for crude β-galactosidase were found at 55 °C and 7.0, respectively, while that dialyzed β-galactosidase were optimized at 50 °C and 7.0. Based on partial purification and characterization, Lactobacillus plantarum B123 is indigenous LAB which good for production of β-galactosidase. Keywords: characterization; dialysis; lactic acid bacteria; Lactobacillus plantarum B 123; β-galactosidase.